1986
DOI: 10.1038/clpt.1986.57
|View full text |Cite
|
Sign up to set email alerts
|

Antipyrine kinetics in liver disease and liver transplantation

Abstract: Antipyrine kinetics were studied in seven normal subjects, 10 patients with liver disease, and 13 clinically stable patients who received a liver transplant. Five patients were studied both before and after liver transplantation. Antipyrine concentrations in saliva after oral dosing were measured by HPLC. The antipyrine t 1/2 was significantly longer (P < 0.05) in patients with liver disease than in patients undergoing liver transplantation and normal subjects. Antipyrine clearance was not significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…1 ). Addition of antipyrine (a negative control), which lacks protein binding capability 27 28 , did not lead to a significant change in uraemic toxin protein binding ( Figs 1 and 2 ).…”
Section: Resultsmentioning
confidence: 93%
“…1 ). Addition of antipyrine (a negative control), which lacks protein binding capability 27 28 , did not lead to a significant change in uraemic toxin protein binding ( Figs 1 and 2 ).…”
Section: Resultsmentioning
confidence: 93%
“…Mehta et al[ 22] reported the antipyrine kinetics in liver disease and liver transplantation. Their results indicate that liver transplantation improves the drug metabolizing ability of patients with liver disease and that the oxidative metabolizing capacity of the liver in clinically stable patients after liver transplantation is similar to that of normal subjects, showing the eligibility of antipyrine clearance test for the patients underwent hepatactomy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of metabolic probes to quantitate the phenotypic expression of CYPs is a widely used approach to study changes in drug metabolism. An early study by our group demonstrated that antipyrine clearance normalized rapidly after OLTx 5 . An extension of these studies included multiple probes for CYP activity.…”
mentioning
confidence: 99%
“…An early study by our group demonstrated that antipyrine clearance normalized rapidly after OLTx. 5 An extension of these studies included multiple probes for CYP activity. The "Pittsburgh cocktail" contains 5 probe drugs for the above CYP enzymes including 100 mg caffeine, 250 mg chlorzoxazone, 100 mg dapsone, 10 mg debrisoquine, and 100 mg mephenytoin, and it is a noninvasive method to evaluate the in vivo phenotype of these enzymes independently and simultaneously.…”
mentioning
confidence: 99%